Periodontite como fator de risco para parto prematuro e nascimento de bebês com baixo peso: Estudo de caso-controle - Massaro, Carla Regina (2018)
Introduction: Periodontitis is considered a public health problem because of its high prevalence in the world and has been associated with preterm birth and low birth weight. Prematurity is one of the most serious perinatal problems, persisting as one of the major causes of perinatal mortality and morbidity. Objective: To evaluate the effect of periodontal disease on preterm birth and the birth of low birth weight babies. Materials and Methods: This is a study involving 45 mothers of newborn infants, assessed periodontally 48 hours postpartum, who presented mild to moderate / severe, localized or generalized chronic periodontitis with probing bleeding and gingival inflammation. Divided into DPL (mild periodontal disease) (n = 15) and DPMS group (moderate / severe periodontal disease) (n = 30). Data were collected from the current gestation and baby data. The variables were tested for normality and homogeneity (Shapiro-Wilk test) and submitted to the Student's T-test (p <0.05). The correlation between variables was analyzed using the Pearson Correlation Test. Results: The results showed that there was a moderate (-0.5388) and significant (p = 0.014) negative correlation between gingival crevicular fluid and gestational age, a moderate (-0.5026) and significant (p = 0.0046) negative correlation between the index of plaque and gestational age and a moderate (-0.4562) and significant (p = 0.0112) negative correlation between gingival index and gestational age in the DPMS group alone. Conclusion: From the results obtained, it was possible to conclude that the presence of inflammation due to moderate / severe periodontitis may represent a risk factor for the occurrence of preterm birth.